SOLUBILITY AND DISSOLUTION RATE ENHANCEMENT OF TELMISARTAN BY SOLID DISPERSION AND PELLETIZATION TECHNIQUES USING SOLUPLUS AS CARRIER - KUNAM, VISWANADH; GARIKAPATI, DEVALA RAO; SURYADEVARA, VIDYADHARA; MANDAVA, VENKATA BASAVESWARA RAO; JANGA, RAMESH BABU; SUNKARA, SIVA PRASAD (International Journal of Applied Pharmaceutics, 2020)
Objective: In the present investigation, an attempt was made to improve the surface characters and solubility of the drug by solid dispersion and coating it on the nonpareil sugar beads as pellets. Methods: Telmisartan solid dispersions were prepared by kneading method using soluplus. Crospovidone was added as disintegrant in pellets. Telmisartan pellets were prepared by dissolving soluplus and crospovidone in ethanol in different ratios and coated on nonpareil sugar beads as a drug layer by pan coating technique. Various physicochemical parameters like particle size, friability, angle of repose and drug content were evaluated for the prepared solid dispersions and pellet formulations. In vitro dissolution studies were carried out in pH 7.5 phosphate buffer using USP apparatus II. Fourier Transform Infrared Spectrometry, Differential Scanning Calorimetry and Scanning Electron Microscopic analysis were performed for solid dispersions, pellet formulations and its polymers to determine the interactions and surface characteristics. Results: The physicochemical parameters were within the specified I. P limits. It was observed that the solid dispersion formulation TS5 containing 1:5 ratio of telmisartan to soluplus showed better dissolution rate to the extent of 1.143 folds and 2.033 folds when compared to a marketed formulation and the pure drug, respectively. Similarly, pellet formulation TP3 containing 1:3 ratio of telmisartan to soluplus showed an improved dissolution rate to the extent of 1.221 folds and 2.170 folds when compared to the marketed formulation and the pure drug, respectively. FTIR and DSC analysis revealed that there was no major interaction between the drug and the excipients. Conclusion: From the present study, it was observed that the solubility of telmisartan was enhanced by soluplus in pellet formulations when compared to solid dispersions.